Effect of foliar spray with Dry Bread Yeast suspension on growth and yield of summer squash (Cucurbita pepo L.)under costal conditions (Latakia University Journal -Biological Sciences Series, 2022)
The research aimed to study the effect of foliar spray with dry bread yeast suspension on growth and yield of summer squash "SYDRA F1 HYBRID".The research was carried out during the spring season of 2021 on Bisaysin village(jablah)lattakia governorate ,the experiment was designed as randomized complete block was with three replicates per treatment, and 15 plants in each replicate . The experiment included four treatments the control and the plants being sprayed with bread yeast suspension by three concentrations ( 4-6 -8 )g ł . The results showed that foliar spray with yeast suspension 8 gł achieved a significant difference as compert to other treatments in term of all studied indicators; it led to a highest values of stem length (43.3) cm , number of leaf (34 ) leaf \plant ,total leaf area (12152 ) cm2\ plant, area index leaf (3.37), number of fruits (25.1 ) fruit\ plant, the yield of plant(3194 )g \ plant and production efficiency (67 )%.